(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the seroprevalence of syphilis in blood donors at the Hemocentro de Sergipe, from 2015 to 2017. The study was carried out by analyzing the records of the Hemocentro de Sergipe obtained in the HEMOVIDA database. 77,791 donations were registered in these intervals, which were submitted to the VDRL test (Veneral Disease Research Laboratory) and confirmatory test with the Enzyme Linked ImmunonoSorbent Assay (ELISA) immunoassay. The prevalence of syphilis found in the Coordinating Blood Center of Sergipe in the analyzed period was 1.4%, which is partially high, when compared to others in Blood Centers distributed throughout the country, being higher among males with 73.7% with educational level. complete high school and single marital status. Although the study does not cover the entire state of Sergipe, the results obtained allow a broader view of the situation of syphilis in the state, contributing as an important source of data for the epidemiological surveys carried out by health agencies and enabling them to direct of your actions.